Serological evidence and factors associated with Crimean–Congo haemorrhagic fever in sheep in Burkina Faso - Dahourou, L.D.; Akio, S.; Savadogo, M.; Yougbaré, B.; Ouoba, L.B.; Tapsoba, A.S.R.; Zerbo, L.H.; Ilboudo, Abdoul K.; Abga, R.L.; Traoré, A.; Dione, Michel M.; Alambédji, R.B. (Wiley, 2024)
Background Crimean–Congo haemorrhagic fever (CCHF) is caused by an orthonairovirus transmitted by bites from infected ticks or by direct contact with blood or tissues of infected ticks, viraemic patients or viraemic livestock.